A study on metaphysics and its influence in commercial building design / Nor Aniswati Awang Lah - Awang Lah, Nor Aniswati (2018)
This thesis presents the findings of a study on functional performance of commercial buildings. Comparison between traditional and modern physical design and planning approaches and practices were carried out by reviewing and analysing selected buildings and premises. The main aim of the study is to gauge if the selected building designs are in compliance with any metaphysical theories. In order to achieve the main aim of the study, three major Asian cultures; the Chinese-Buddhist, IndianHindu, and Malay-Islam, are reviewed on metaphysical approaches in building design. It was found that there are similarities in principles towards achieving the occupants' well-being. Functionality is prioritised and rituals are performed at ensuring the wellbeing and prosperity of future occupants. The Chinese-Buddhist practice is based on Feng Shut, the Indian-Hindu tradition is based on Vastu-Vidya and the Malay-Islam exploits religious teachings written in a manuscript titled Tajul Muluk. Comparisons between traditional and modern physical design and planning approaches and practices were made by reviewing and analysing current and selected buildings or premises. A total number of 15 commercial premises were identified and these were categorized under the labels "performing", "non-performing" and "benchmark performance". An observational procedure was devised in the analysis process, which was based on technique done previously by others. The findings reveal some evidence that metaphysics had certain influence towards functional performance of the commercial buildings. The results seemly suggested that the metaphysical approach in planning and design could be considered to complement the modern design practices. However, further analysis needs to be carried out involving larger number of samples and area coverage to confirm the findings of the present study. The overall findings of the study allowed for an 'indicator' on the functional performance for building design been established. The 'indicator' can be used to assist the performance of different types of buildings together with other suggestions and recommendations. It is believed that the 'indicator' may be useful in enhancement of building functional performance as well as to improve the social environment of the community living in the built environment.